Moral Education for Women (an Analysis of Qur'an Surat An-Nur Verse 31) - Febriani, Evi; Aulia, Rahma; Rahmatusiam, Oktavina; Halisah, Nurul; Agustina, Putri Andriani; Janah, Nursila Fiqi Alia Fedrotul (Pusdikra-Publishing.com, 2025)
This study examines the importance of moral education for women, based on the teachings of Surah An-Nur, verse 31 in the Qur'an. The study aims to understand how Islamic education emphasizes moral cultivation as a guide for women, particularly in maintaining dignity and ethical conduct. Moral education in Islam focuses not only on personal aspects but also on social responsibility, aiming to develop women’s character with strong faith, piety, and moral integrity. This research employs a library study method with content analysis to explore relevant literature. The findings indicate that teachings on controlling one’s gaze, covering one’s body, and dressing modestly are fundamental in preserving women’s dignity. Moral education serves not only as a behavioral guide but also as a means of building a positive character that adapts to social changes.Overall, moral education for women in Islam is a comprehensive, continuous process. It aims to shape women who not only embody religious values but also contribute positively to society. This study offers insights into how moral education plays an essential role in strengthening the identity of Muslim women and supporting the creation of a more harmonious society.